Advanced biological imaging techniques based on metasurfaces - Yongjae Jo; Hyemi Park; Hyeyoung Yoon; Inki Kim (Opto-Electronic Advances)
Advanced imaging techniques have been widely used in various biological studies. Currently, numerous imaging modalities are utilized in biological applications, including medical imaging, diagnosis, biometrics, and fundamental biological research. Consequently, the demand for faster, clearer, and more accurate imaging techniques to support sophisticated biological studies has increased. However, there is a limitation in enhancing performance of imaging devices owing to the system complexity associated with bulky conventional optical elements. To address this issue, metasurfaces, which are flat and compact optical elements, have been considered potential candidates for biological imaging. Here, we comprehensively discuss the metasurface empowered various imaging applications in biology, including their working principles and design strategies. Furthermore, we compared conventional imaging modalities with the metasurface-based imaging system. Finally, we discuss the current challenges and offer future perspectives on metasurfaces.